2017
DOI: 10.1159/000455115
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Markers and Histologic Subtypes in Patients with Meningeal Carcinomatosis in Breast Cancer

Abstract: Objective: Meningeal carcinomatosis (MC) is a rare complication in breast cancer patients. It is defined as a diffuse or multifocal leptomeningeal metastasis. Study Design: From our institution database, we retrospectively studied 19 patients diagnosed with MC in the cerebrospinal fluid (CSF) in 1997-2015, in order to evaluate tumor prognostic markers, histologic subtypes, and clinical outcome. Results: All patients were female, with a mean age of 53 years (range 36-75 years). The mean interval between diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Interestingly, Zebrowski et al ( 407 ) suggested a potential association between the inability of trastuzumab to cross the blood-brain barrier and the occurrence of intramedullary metastases in Her2 positive disease. Additionally, some studies report a predisposition of lobular histotype to leptomeningeal carcinomatosis, whilst in the case of ductal carcinoma spreading to the meninges a high histological grade and triple-negative biology seems to be prevalent ( 394 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Zebrowski et al ( 407 ) suggested a potential association between the inability of trastuzumab to cross the blood-brain barrier and the occurrence of intramedullary metastases in Her2 positive disease. Additionally, some studies report a predisposition of lobular histotype to leptomeningeal carcinomatosis, whilst in the case of ductal carcinoma spreading to the meninges a high histological grade and triple-negative biology seems to be prevalent ( 394 ).…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer remains one of the leading cancer types by diagnosis, and cases have been steadily rising over the past decades [ 17 ]. While meningeal carcinomatosis (MC) is a rare metastatic outcome occurring in roughly 1–5% of solid tumors, primary breast tumors, along with lung tumors and melanoma, make up the most common origin sites [ 18 ]. Among studies of patients with leptomeningeal breast cancer metastasis (LBM), the average age of breast cancer diagnosis is often between 50 and 60 [ 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Breast Cancermentioning
confidence: 99%
“…While meningeal carcinomatosis (MC) is a rare metastatic outcome occurring in roughly 1–5% of solid tumors, primary breast tumors, along with lung tumors and melanoma, make up the most common origin sites [ 18 ]. Among studies of patients with leptomeningeal breast cancer metastasis (LBM), the average age of breast cancer diagnosis is often between 50 and 60 [ 18 , 19 , 20 , 21 , 22 , 23 ]. Once diagnosed, the average time to develop LBM is less than 10 years [ 19 , 23 ].…”
Section: Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation